Ekosistem Bisnis Daur Ulang Sampah Plastik Oleh UMKM Menuju Peningkatan Ekonomi Hijau - Galang Regina Rifal; Rezi Rahman Dispindra; Antoni Ludfi Arifin; Ahmad Azmy (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
The issue of plastic waste is still a national and global problem. The importance of managing plastic waste and knowing the role of the plastic waste recycling management business ecosystem to support the improvement of the green economy. This study aims to analyze the role of the circular economy-based business ecosystem in plastic waste management in Indonesia and the opportunities for improving the green economy. By involving collectors, communities, governments, and MSMEs in the recycling chain, this approach seeks to reduce plastic waste that pollutes the environment while creating added economic value. This study uses a qualitative method with a literature study approach by collecting and analyzing more than 50 relevant academic sources to explore the role of each stakeholder and the supporting or inhibiting factors for the implementation of the circular economy system. The results of the study show that public education, government support through regulations and incentives, and collaboration between stakeholders are very important in creating a sustainable ecosystem. With consistent implementation, this ecosystem has great potential to drive Indonesia towards a more inclusive and sustainable green economy.